KOMUNIKASI ETNOGRAFI PADA SERAH-TERIMA MANTEN PERNIKAHAN ADAT JAWA DI KECAMATAN MAPPEDECENG, KABUPATEN LUWU UTARA, SULAWESI SELATAN - Eva Zulfiah Hasanah (ppjbsip, 2022)
Abstract: This research uses the ethnographic method of communication, which is a study that examines the role of language in the communicative behavior of a society. The subjects in this study were several informants and two resource persons who were the main actors in the handover tradition of the manten. The object under study is the manten handover tradition. This study aims to reveal the ethnography of communication on the tradition of handing over manten in Javanese wedding customs in Mappedeceng District, North Luwu Regency, South Sulawesi. And disclose the registers used in the tradition. The results showed that the communication ethography of SPEAKING Dell Hymes in the form of setting took place at the bride's house. Participants are the bride and groom, close relatives, KUA officers, community leaders and religious leaders. Ends or the goal is to establish harmony between the two family families, Act Sequence in the form of surrender first, then acceptance. The rules of interaction in this tradition are to pay attention to several things including: the presence of the bride and groom, the presence of the families of the bride and groom, there are guardians and witnesses of each marriage, the most important thing is the spokesperson for each